2021
DOI: 10.1177/0961463x211027420
|View full text |Cite
|
Sign up to set email alerts
|

Disrupting times in the wake of the pandemic: Dispositional time attitudes, time perception and temporal focus

Abstract: Introduction The COVID-19 pandemic has majorly disrupted many aspects of people’s lives, provoking psychosocial distress among students. People’s positive and negative attitudes towards the past, present and future were a dispositional pre–COVID-19 reality. Faced with a pandemic, people have reported disruptions in the speed of passing time. People can shift their attention more towards the past, present or future when major changes in society occur. These aspects of psychological time would be key to understa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
34
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 49 publications
(76 reference statements)
6
34
0
1
Order By: Relevance
“…Time judgment is therefore a good -and easy-to-measure -indicator of psychological health. However, time judgment assessed in our study was only one component of time judgment which encompasses different subjective time experiences, like interval duration estimation or the perceived speed of time passage as that examined in our studies (see Loose et al, 2021). In sum, our studies on this specific component of time judgment have shown that, as of the first lockdown, individuals have experienced no further variation in the speed of the passage of time, which has always been found to have stagnated or to be flowing slowly.…”
Section: Discussionmentioning
confidence: 96%
“…Time judgment is therefore a good -and easy-to-measure -indicator of psychological health. However, time judgment assessed in our study was only one component of time judgment which encompasses different subjective time experiences, like interval duration estimation or the perceived speed of time passage as that examined in our studies (see Loose et al, 2021). In sum, our studies on this specific component of time judgment have shown that, as of the first lockdown, individuals have experienced no further variation in the speed of the passage of time, which has always been found to have stagnated or to be flowing slowly.…”
Section: Discussionmentioning
confidence: 96%
“…Complementing the European studies, a subjective expansion of time was related to negative emotions, such as loneliness. A study in Uruguay among university students [ 9 ] assessed different measures, including the passage of time (e.g., “My days pass more slowly, time extends.” and “My days pass more quickly, time flies.”). They reported similar results: an association of psychological distress due to COVID-19 restrictions with a felt slower passage of time, a blurred sense of time (not knowing what time or day it was), and more boredom.…”
Section: Introductionmentioning
confidence: 99%
“…Research conducted in Europe and South America suggests that a commonly reported consequence of life during covid-19 is distortion to the passage of time [ 3 – 12 ]. Studies conducted in the UK [ 3 , 4 ], France [ 5 , 6 ], Italy [ 7 , 8 ], Uruguay [ 9 ] and Argentina [ 10 ], in which people were asked to compare speed at which time was passing during the pandemic to before the pandemic, have reported widespread and significant distortion to the passage of time during the covid-19 pandemic in comparison to prior to the covid-19 pandemic. Distortions are not limited to any particular age group or gender [ 3 8 ].…”
Section: Introductionmentioning
confidence: 99%